2013
DOI: 10.1007/s00127-013-0748-1
|View full text |Cite
|
Sign up to set email alerts
|

Use transition between illegal drugs among Brazilian university students

Abstract: This study supports the role of the use of marijuana and inhalants almost exclusively before the use of other illicit drugs, whereas the use of ecstasy has an opposite role. These roles could be linked to the prevalence of lifetime use and whether individuals were at an earlier or later age during experimentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
14
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 50 publications
6
14
0
1
Order By: Relevance
“…The response rate of this study was 66%, which may lead to possible selection bias. However, in studies with this population, similar or even lower response rates have been observed 23,24 . Students who did not answer only questions related to the outcome of the present study (n = 255) differed from those who answered (n = 1,123) only for the independent variables age, maternal education in years, and body satisfaction.…”
Section: Discussionsupporting
confidence: 61%
“…The response rate of this study was 66%, which may lead to possible selection bias. However, in studies with this population, similar or even lower response rates have been observed 23,24 . Students who did not answer only questions related to the outcome of the present study (n = 255) differed from those who answered (n = 1,123) only for the independent variables age, maternal education in years, and body satisfaction.…”
Section: Discussionsupporting
confidence: 61%
“…Considering that adolescence is a period of experimentation with various drugs (Malta et al, 2010), the subsequent period (university or college years) may be of interest to access the sequence of experimentation of with these drugs. In a previous analysis using the sample of the present study, the average age of first use of each of the nine drugs analyzed in this study was between 15.2 and 21.2 years (Castaldelli-Maia et al, 2014b). …”
Section: Introductionmentioning
confidence: 61%
“…Although emergency settings are not the ideal place to treat chronic problems of substance use, they can be an important font of information of both patient profi le and changes in International Review of Psychiatry, August 2014; 26(4): 508-514 ICD-10 mental and behavioural disorders due to use of cocaine 509 their consumption patterns, since it is generally the only setting where these individuals get in touch with health services (Galicia et al, 2014). Patients seeking an emergency department for treating acute intoxication with cocaine/crack can present several clinical complications and intoxication with other drugs, since multiple drug use is common, especially in Brazil (Castaldelli-Maia et al, 2014;Oliveira et al, 2013). However, the clinical approach in emergency settings is challenging.…”
Section: Introductionmentioning
confidence: 99%